With Ortega: the essay as an alternative to a philosophy of tightrope walkers (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
The essay (as literary genre) and the Spanish essay (in its historical specificity) are subjects of study with a special force in contemporary criticism. This paper examines the origins of the essay in Spanish literature in Ortega y Gasset, understanding it as a stylistic form of reflection that is not strictly systematic. Despite the existence of important predecessors, with Ortega the essay comes to recognize itself as the form of a new philosophical approach that is justified precisely in its dynamism.
Keywords: Diary; Pla; Vital reason; Positivism; Mediterranean